Fostering Teachers’ Multicultural Competence for Chinese Ethnic Minority Education: An Analysis of Teacher Education Programmes, Syllabuses and Teacher Educator Perceptions - Wang, Wei (Frontiers in Psychology, 2022)
The multicultural characteristics of students belonging to ethnic minorities in China pose challenges for teachers. Teacher competence in dealing with culturally diverse students has been extensively discussed in international scholarship and referenced by Chinese researchers, but there is limited empirical research on how teacher education programmes in China respond to this challenge and theoretical discussions. Based on content analysis on teacher education programmes and syllabuses, as well as expert interviews with four teacher educators at two teacher education institutions, this study investigates how the cultivation of multicultural competence is incorporated into teacher education programmes, and the external forces that shape it. Drawing on international scholarship on teachers’ multicultural competence and Cochran-Smith’s framework on external forces influencing multicultural teacher education practices, I argue that the cultivation of teachers’ multicultural competence for their future work in ethnic minority education is, to a great extent, missing from teacher education programmes. Furthermore, what pre-service teachers’ competence covers, and the external forces that influence how teacher education plays out in practice, are influenced and somewhat determined by the large social, economic and political context as well as the agenda for educational reform in China.